2017
DOI: 10.1038/s41598-017-14652-x
|View full text |Cite
|
Sign up to set email alerts
|

HBeAg-induced miR-106b promotes cell growth by targeting the retinoblastoma gene

Abstract: Chronic HBV infection is a major cause of hepatocellular carcinoma (HCC). The association between hepatitis B “e” antigen (HBeAg) and HCC is well-established by epidemiological studies. Nonetheless, the biological role of HBeAg in HCC remains enigmatic. We investigate the role of HBeAg in HBV-related HCC. Our findings suggest that HBeAg enhances cell proliferation and accelerates progression from G0/G1 phase to the S phase of the cell cycle in Huh7 cells. Examination of host gene expression and miRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…Although the abnormal expression of miRNAs in HCC was regarded as a cause of HCC, we need to further explore the potential mechanism of the impact of miRNA on the progression of HCC. Previous findings showed that miRNA-106b expression is obviously increased in HCC and may provide a new biomarker for the early diagnosis of HCC ( 18 ). Those findings are in line with those of our study showing that miR-106b was overexpressed in HCC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the abnormal expression of miRNAs in HCC was regarded as a cause of HCC, we need to further explore the potential mechanism of the impact of miRNA on the progression of HCC. Previous findings showed that miRNA-106b expression is obviously increased in HCC and may provide a new biomarker for the early diagnosis of HCC ( 18 ). Those findings are in line with those of our study showing that miR-106b was overexpressed in HCC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study has shown that in the progression of cervical cancer, DAB2 was confirmed as a target of miR-106b ( 17 ). Another recent study showed that miRNA-106b expression was markedly increased and regulated HCC development by targeting mRNA ( 18 , 19 ). However, whether miR-106b targeted DAB2 in the regulation of HCC progression has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…HBeAg is a soluble protein in the core particles of HBV, which is processed from the precore protein (27). A number of studies have reported that HBeAg serves a critical role in chronic HBV infection treatment, prognosis and disease progression (28,29). Patients with seropositive HBeAg have an increased risk to develop cirrhosis and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Then five of these miRNAs were selected for qRT‐PCR validation in a larger cohort, and four of them showed similar expression pattern as those revealed by sequencing data, which indicated a low false discovery rate of our sequencing data and supported the credibility of the profile. Among these differentially expressed miRNAs, hsa‐miR‐99b‐3p, ‐451a, ‐15b‐5p, ‐25‐3p, ‐92a‐3p, ‐106b‐3p, ‐1‐3p, and ‐30a‐5p were also differentially expressed in other stages of HBV infection.…”
Section: Discussionmentioning
confidence: 99%